Skillful Disposition and Responsiveness in Mental Imagery - An, Christopher Joseph G (Archīum Ateneo, 2019)
This paper aims to explore and expand on Wittgenstein’s remarks on the nature of mental imagery. Despite some rather cryptic passages and obvious objections, his notion of mental imagery as possessing a constitutive (and not merely added) element of expressive thought and conceptuality offers critical insights linking perceptual capacities with our shared practices. In particular I seek to further develop Wittgenstein’s claim that perceptual impressions presuppose a “mastery of a technique.” I argue that this sense of technique, understood as acquired conceptual capacities, can explain and capture the rich and varied spectrum of expressive visual content that can be accessed by human beings initiated and embedded in a variety of shared practices. Using Gilbert Ryle’s account of dispositions, I cash out the notion of acquired conceptual capacities as spanning a wide latitude of responsive dispositions from mere “blind” visual habits to more normativelyguided, intelligent, and deliberately-trained visual “skills.” Visual impressions construed as such are hardly perceptually (nor representationally) univocal and instead exhibit a dynamic and reflexive plurivocity manifested through one’s initiation into shared practices and forms of life. This plurivocity makes possible a rich array of visual affordances that would otherwise not be accessible outside the context of a shared practice. This suggests that human beings possess a distinctive kind of expressive and responsive intelligence which picks out visual affordances determined not so much by a merely receptive perceptual faculty but by the subject’s skillful, active, and responsive engagement with the world.